Repetitive transcranial magnetic stimulation for enhancing motor function after spinal cord injury: a narrative review - Benavides, Francisco; Shine, Mary Grace; Stefanovic, Filip; Chen, Robert; Jo, Hang Jin (Frontiers in Neurology, 2025)
Spinal cord injury (SCI) often leads to disabilities that significantly impact quality of life, highlighting the need for effective rehabilitation strategies. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising neuromodulatory approach to enhance neuronal plasticity and promote motor recovery following SCI. This narrative review examines the current state of evidence regarding the therapeutic use of rTMS for motor function recovery after SCI and outlines key methodological considerations to guide future research. To address these aims, we summarize various rTMS techniques and evaluate their overall efficacy in improving motor function in individuals with SCI. Among the fourteen studies reviewed, early rTMS protocols primarily utilized low-frequency stimulation, whereas more recent approaches have adopted higher frequencies and more complex patterned protocols. Despite considerable heterogeneity in stimulation parameters, most studies reported beneficial effects of rTMS, including reduction in spasticity and improvements in voluntary motor function of both upper and lower limbs. These findings demonstrate that rTMS holds promise as an effective tool for SCI rehabilitation, with limited to moderate evidence supporting reductions in spasticity, increased muscle strength, and enhanced functional outcomes. However, many of these findings are derived from small sample sizes, varied protocols, and studies lacking rigorous control conditions. The review emphasizes the need for standardized functional and electrophysiological assessments to systematically evaluate motor outcomes following rTMS interventions. Additionally, larger, well-controlled clinical trials incorporating consistent physical therapy protocols are essential to confirm the efficacy of rTMS.